The biogeochemistry of marine nitrous oxide - Frame, Caitlin H (Massachusetts Institute of Technology, 2011)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), June 2011. "June 2011." Cataloged from PDF version of thesis. Includes bibliographical references. Atmospheric nitrous oxide N₂O concentrations have been rising steadily for the past century as a result of human activities. In particular, human perturbation of the nitrogen cycle has increased the N₂O production rates of the two major sources of this greenhouse gas, soil and the ocean. Nitrification, and particularly ammonia oxidation, is one of the major processes that produces N₂O in the ocean. In this thesis, a series of stable isotopic methods have been used to characterize the biogeochemical controls on N₂O production by marine nitrification as well as the natural abundance stable isotopic signatures of N₂O produced by marine nitrifiers. This thesis shows that in addition to chemical controls on N₂O production rates such as oxygen (O₂) and nitrite (NO₂- ) concentrations, there are also biological controls such as nitrifier cell abundances and coastal phytoplankton blooms that may influence N₂O production by ammonia oxidizers as well. Ammonia oxidizers can produce N₂O through two separate biochemical mechanisms that have unique isotopic signatures. Using culture-based measurements of these signatures, we conclude that one of these pathways, nitrifier-denitrification, may be a significant source of N₂O produced in the South Atlantic Ocean and possibly the global ocean. by Caitlin Frame. Ph.D.